A Patent Review on the Use of L-Asparaginase in the Treatment of Acute Lymphocytic Leukemia - Freire, Davi A.; Lisboa Magalhães, Ilana Carneiro; Tramontina Florean, Eridan O. P.; Florindo Guedes, Maria Izabel (Recent Advances in Drug Delivery and Formulation, 2021)
L-asparaginase (L-asparagine amino hydrolase, E.C.3.5.1.1) is the most important chemotherapeutic drug used in treating Acute Lymphocytic Leukemia (ALL), decreasing blood asparagine rates causing apoptosis in tumor cells. However, pharmacological drugs cause several side effects making treatments difficult. Thus, searches for new sources of L-asparaginase or enzyme modifications focus on discovering new products to use in therapy. This article reviewed published patents from 2000 to 2020 related to the treatment of ALL using L-asparaginase. Many organisms have been shown as potential viable L-asparaginase producers for use in the treatment of ALL. However, this patent review shows that few of these organisms are gaining attention to becoming bioproducts for the market. It is expected that drugs in the testing phase and patents related to the treatment of ALL and other cancers will become real products. Besides, a treatment using an amino acid depletion approach, now referring to asparagine, altogether with a compound that directly interferes with the expression of the asparagine synthase gene, is more suitable for the treatment of ALL and possibly to other cancers.
Keywords: products